Microstructural evolution of nanometric Ti(NiCu)2 precipitates in annealed Ni–Ti–Cu thin films. (July 2015) - Callisti, M.; Polcar, T.
Abstract: A sputter deposited Ni–Ti–Cu thin film was annealed for 1 h at 500 and 600 °C and its microstructure investigated by transmission electron microscopy and focused ion beam. Annealing at higher temperatures caused a remarkable microstructural evolution of the nanometric Ti(NiCu)2 plate precipitates formed inside the grains. Precipitate coarsening occurred in the inner part of the grains according the Ostwald ripening effect, while close to the grain boundaries, solute atoms preferentially diffused towards grain boundaries, thus causing local precipitates depletion. The density distribution of metastable precipitates in the grain interior of annealed Ni–Ti–Cu films depends on the distance from grain boundary. Highlights: Ti(NiCu)2 plate precipitates coarsen with increasing annealing temperatures. Precipitate coarsening in the grain interior follows the Ostwald ripening effect. Solute atoms preferentially diffuse from precipitates to near grain boundaries.